Follow-up of iatrogenic aorto-coronary "Dunning" dissections by cardiac computed tomography imaging - Baumann, Stefan; Behnes, Michael; Sartorius, Benjamin; Becher, Tobias; El-Battrawy, Ibrahim; Fastner, Christian; Ansari, Uzair; Loßnitzer, Dirk; Henzler, Thomas; Schönberg, Stefan; Borggrefe, Martin; Akın, Ibrahim (BMC medical imaging, 2017)
Iatrogenic aorto-coronary dissections following percutaneous coronary interventions (PCI) represent a rare but potentially life threatening complication. This restrospective and observational study aims to describe our in-house experience for timely diagnostics and therapy including cardiovascular imaging to follow-up securely high-risk patients with Dunning dissections.